If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6 = 7y + -1y Combine like terms: 7y + -1y = 6y 6 = 6y Solving 6 = 6y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-6y' to each side of the equation. 6 + -6y = 6y + -6y Combine like terms: 6y + -6y = 0 6 + -6y = 0 Add '-6' to each side of the equation. 6 + -6 + -6y = 0 + -6 Combine like terms: 6 + -6 = 0 0 + -6y = 0 + -6 -6y = 0 + -6 Combine like terms: 0 + -6 = -6 -6y = -6 Divide each side by '-6'. y = 1 Simplifying y = 1
| f(x)=xln(2)+6 | | 4y-48=30 | | 9x^2+2x-14=0 | | 8x*12=5 | | Y=x^3-x^2-21x+45 | | 3-2x-5xy= | | 31x-7+66=180 | | 13602.48=2*3.14*r^2+2*r*95 | | 3(4x+8)-5x=3 | | 3sin^2x=4(1-sinx) | | 3(x+9)=3(5x-5)+2x | | 9=33b | | 97.5/100=50/x | | -16+(-17)+(-18)+10= | | 2 = u4– 2 | | 4(-7x+3)=-128 | | 0.18(y-4)+0.06y=0.16y-0.6 | | 6y-8y+6y= | | 7(3x+8)=182 | | 5(3x+5)=3(5x+10) | | x^2-4xy=3y^3 | | 2x^2-16+3x^2=180 | | -22+20+2+(-18)= | | 2v/3=24 | | 5e^9x=9 | | 5e^9*x=9 | | -5x-10=-7x+6 | | 4-6x=4+6x | | 10x+2=4(2x-3) | | 8m-2=-3 | | 2.5(10x+8)+3x= | | 10x-2=4(2x-3) |